Forecast of Economic Growth in Armenia - Mkrtchyan, Anahit; Petrosyan, Gevorg (ՀՀ ԳԱԱ)
The article presents the development of methods for forecasting economic growth. Since the 1950s, researchers have paid more attention to economic growth research. Many analysts and economists have focused on methods of forecasting economic growth and have tried to find the principal methods that influenced it. In the 2000s, economists found out that more than 500 exogenous or indigenous factors affect economic growth. Every national economy has its specifications which makes the forecast of its economic growth uncorrelated with the others. Some of them are heavily affected by oil and gas production, the others – by financial or customer service and a dozen of influenced national economies are affected by the production in agriculture Հոդվածում ներկայացված է տնտեսական աճի կանխատեսման մեթոդների զարգացումը։ Հետազոտողները տնտեսական աճի հետազոտություններին առավել մեծ ուշադրություն սկսել են դարձնել անցյալ դարի 50-ական թվականներից։ Բազմաթիվ վերլուծաբաններ և տնտեսագետներ իրենց աշխատանքներում անդրադարձել են տնտեսական աճի կանխատեսման մեթոդներին և փորձել գտնել այն գործոնները, որոնք ազդում են տնտեսական աճի վրա։ 2000-ական թվականներին տնտեսագետները գտել էին ավելի քան 500 էկզոգեն և էնդոգեն գործոններ, որոնք ազդում էին տնտեսական աճի վրա։ В статье представлена разработка методов прогнозирования экономического роста. С 1950-х годов исследователи уделяют больше внимания исследованиям экономического роста. Многие аналитики и экономисты уделяли внимание методам прогноза экономического роста и пытались найти те главные методы, которые влияли на него. В 2000-х годах экономисты нашли более 500 экзогенных и индогенных факторов, влияющих на экономический рост. Каждая экономика имеет свои спецификации, которые делают прогнозирование экономического роста этой страны некоррелированным с прогнозами экономических рост других стран.
Keywords: Economics